An Investigation into Metonymy used in Truyen Kieu by Nguyen Du and Its Translational Versions in English by Huynh Sanh Thong and Michael Concell - Ha Thi Hoai Thanh
Chapter 1 Introduction; Chapter 2 Literature review and theoretical background; Chapter 3 Research design and methodology; ...